Deterrence of nuclear terrorism in the context of South Asia. Issue 4 (1st October 2016) - Modongal, Shameer
ABSTRACT: Stability among the great powers during the Cold War is widely theorized in terms of nuclear deterrence. Rationality of states and their preference for survival are the basis of nuclear deterrence. The rationality of non-state terrorist groups is different from that of nation-states. Even though they are also rational actors with their own hierarchy of preferences, survival may not be their ultimate goal. Deterrence of nuclear terrorism is therefore different from deterrence against states. South Asia is more vulnerable to nuclear terrorism than any other region of the world for many reasons. This article analyzes the possibility of nuclear terrorism and the ways of deterrence against it in the context of South Asia.